Integration of Health Information Systems in Developing Countries: A Systematic Review of Quality, Performance, and Competency Evaluation - Albertus Yudha Poerwadi; Yunia Wardi; Rino Rino (JURNAL INFO KESEHATAN, 2025)
Persistent challenges in health workforce planning, distribution, and performance management remain prevalent in developing countries, largely due to fragmented and underutilized human resource data systems. Human Resource Information Systems (HRIS) have emerged as a strategic tool to support evidence-based decision-making and strengthen health workforce governance. This Systematic Literature Review (SLR) synthesizes empirical evidence published between 2015 and 2024 on the role of HRIS in enhancing strategic health workforce management in developing countries, with the objectives of identifying key Information System (IS) evaluation models, examining the relationship between system quality and individual performance, exploring the integration of competency planning and Person–Job Fit (P–J Fit), and highlighting critical research gaps. A systematic review of 20 peer-reviewed studies was conducted following the PRISMA protocol, encompassing system design foundations, adoption processes, interoperability challenges, and workforce-related outcomes in healthcare settings. The findings indicate that HRIS functions as a strategic enabler for decentralized management, evidence-based workforce planning, and performance improvement; however, its effectiveness is constrained by persistent interoperability barriers, fragmented data architectures, and the absence of internationally standardized workforce data. In conclusion, maximizing the strategic value of HRIS requires a dual emphasis on data standardization and organizational readiness, while future research should integrate behavioral theories with IS success frameworks, assess long-term HRIS impacts, and foster international collaboration to establish unified health workforce data standards that support policy coherence and digital health transformation in the public sector.